Catching fire - Collins, Suzanne (The Hunger Games trilogy, 2009)
By winning the annual Hunger Games, District 12 tributes Katniss Everdeen and Peeta Mellark have secured a life of safety and plenty for themselves and their families, but because they won by defying the rules, they unwittingly become the faces of an impending rebellion.